2007
DOI: 10.1128/jb.01803-06
|View full text |Cite
|
Sign up to set email alerts
|

Sinorhizobium meliloti SyrA Mediates the Transcriptional Regulation of Genes Involved in Lipopolysaccharide Sulfation and Exopolysaccharide Biosynthesis

Abstract: Sinorhizobium meliloti is a gram-negative soil bacterium found either in free-living form or as a nitrogenfixing endosymbiont of leguminous plants such as Medicago sativa (alfalfa). S. meliloti synthesizes an unusual sulfate-modified form of lipopolysaccharide (LPS). A recent study reported the identification of a gene, lpsS, which encodes an LPS sulfotransferase activity in S. meliloti. Mutants bearing a disrupted version of lpsS exhibit an altered symbiosis, in that they elicit more nodules than wild type. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
11
1
Order By: Relevance
“…The B. abortus bvrS/bvrR system may be required for virulence, because it controls the expression of several outer membrane proteins and is involved in modulating the properties of bacterial lipopolysaccharide 162,167 . It has not been possible to construct null mutants of the S. meliloti homologues of these genes, exoS and chvI, indicating that they are essential 32,168 . However, a mutant that produces a constitutively active ExoS sensor kinase is partially impaired in its ability to infect root hairs (see main text) [31][32][33] .…”
Section: Box 3 Host Invasion Parallels Between Rhizobia and Animal Pamentioning
confidence: 99%
“…The B. abortus bvrS/bvrR system may be required for virulence, because it controls the expression of several outer membrane proteins and is involved in modulating the properties of bacterial lipopolysaccharide 162,167 . It has not been possible to construct null mutants of the S. meliloti homologues of these genes, exoS and chvI, indicating that they are essential 32,168 . However, a mutant that produces a constitutively active ExoS sensor kinase is partially impaired in its ability to infect root hairs (see main text) [31][32][33] .…”
Section: Box 3 Host Invasion Parallels Between Rhizobia and Animal Pamentioning
confidence: 99%
“…Changes common to all three transcriptomes include increased expression of the exo genes, sinI N-acyl-L-homoserine lactone synthetase, eglC glycanase, and genes of unknown function (see Data set S1 in the supplemental material). Ptrp-syrA was previously shown to increase expression of exoY-, exoH-and exoF-uidA gene fusions (69). In S. meliloti strains bearing an intact expR, SinI is required for quorum sensing via long-chain acyl homoserine lactones; sinI mutants do not show swarming motility and are less efficient at forming nodules than the wild type (70,71).…”
Section: Nodd3mentioning
confidence: 99%
“…Therefore, LsrB is a new LysR family regulator that is associated with LPS production. Moreover, LsrB appears to modify only the amount of LPS, not its constituents, as is the case with SyrA and TtsI (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…SyrA in S. meliloti and TtsI in S. fredii NGR234 contribute to the regulation of LPS O-antigen synthesis (15,16). It also has been reported that the transcription elongation factor GreA participates in LPS core biosynthesis in S. meliloti 1021 and S. fredii HH103 (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation